1995
DOI: 10.1159/000188521
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochemical Profile of Visceral Mesothelium under the Influence of Lactated-Hyperosmolar Peritoneal Dialysis Solutions

Abstract: Male albino mice had one daily intraperitoneal injection of 4.25 g/100 ml glucose concentration fluid for peritoneal dialysis at pH 5.0-5.2, for a period of 30 days. At the end of the experimental periods, mesothelial cell imprints were taken from the peritoneal layer of the anterior liver surface. Histochemical staining of imprints obtained from mice exposed to the peritoneal dialysis fluid showed a consistently increased activity of: (a) enzymes associated with the cell membrane: Na-K-ATP-ase, alkaline phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Additionally, the substantially higher prevalence of nonviable cells in monolayers exposed to glucose is a clear suggestion that factors other than a high osmolar concentration are to be invoked to explain the alterations observed in the mesothelium. So far, it appears that the hypertrophic phenotype observed in monolayers exposed to high glucose solutions finds its origin in the metabolic effects induced by glucose itself [1, 4, 6, 30, 31], and/or by toxicity from the presence of products derived from the Maillard reaction in the dialysis solution [9, 10, 11]promoting, in turn, the permanent challenge of oxidative stress [32, 33, 34, 35]. It should be noticed that the hypertrophic phenotype, associated with the use of a high-glucose concentration, was observed regardless of the pH of the solution [5], or whether the buffer was lactate or bicarbonate [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the substantially higher prevalence of nonviable cells in monolayers exposed to glucose is a clear suggestion that factors other than a high osmolar concentration are to be invoked to explain the alterations observed in the mesothelium. So far, it appears that the hypertrophic phenotype observed in monolayers exposed to high glucose solutions finds its origin in the metabolic effects induced by glucose itself [1, 4, 6, 30, 31], and/or by toxicity from the presence of products derived from the Maillard reaction in the dialysis solution [9, 10, 11]promoting, in turn, the permanent challenge of oxidative stress [32, 33, 34, 35]. It should be noticed that the hypertrophic phenotype, associated with the use of a high-glucose concentration, was observed regardless of the pH of the solution [5], or whether the buffer was lactate or bicarbonate [36].…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations using the in vivo and in situ model of population analysis of mesothelium showed that dialysis solutions, containing high concentrations of glucose, induced drastic changes in the phenotype of the mesothelial monolayer: basically, increased activity of cytoplasmic and cell membrane-associated enzymes [4], and marked hypertrophic changes characterized by expanded cytoplasmic surface area, increased multinucleation and reduced mitotic activity [5, 6]. These changes, identifying a population of senescent cells with low regenerative potential, were correlated with the concentration of glucose in the dialysis fluid, but not with the low pH [4]or with the presence of lactate buffer [7, 8]. If so, we thought that it would be pertinent to study the way(s) by which a physiological agent such as glucose, in a high concentration, could be the origin of these unwanted effects upon the exposed monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the monolayer showed poor regenerative capabilities, as suggested by the low incidence of mitoses [17]. Histochemical staining done on the same experimental model revealed a substantially increased enzymatic activity [16]. These tracts characterize a population of hypertrophic senescent cells, near the end of its in vivo developmental life span [35, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…The whole paper was weighed using an analytic scale (type 2474; Sartorius, Göttingen, Germany), and, after separation with scissors, the individual surface area of each cell was calculated as a function of its weight in relation to the weight of the whole piece of paper (approximately 800 mg). The limit between normal-size and large cells was fixed at 518.80 µm 2 of surface area [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation